Anaesthesia with sevoflurane in pigeons: minimal anaesthetic concentration (MAC) determination and investigation of cardiorespiratory variables at 1 MAC. (28th May 2016) - Botman, J.; Gabriel, F.; Dugdale, A. H. A.; Vandeweerd, J.‐M.
Abstract : The objective of the study was to determine the minimal anaesthetic concentration (MAC) of sevoflurane (SEVO) in pigeons and investigate the effects of 1 MAC SEVO anaesthesia on cardiovascular and respiratory variables compared with the awake state. This is a prospective, experimental study. Animals were seven healthy adult pigeons. After acclimatisation to handling, heart rate (HR), heart rhythm, respiratory rate ( f R), end‐expired carbon dioxide tension (PE′CO2 ), inspired CO2 tension, indirect systolic arterial blood pressure (SAP) and cloacal temperature were measured to determine baseline, 'awake' values. Pigeons were then anaesthetised with SEVO and MAC was determined by the 'bracketing' method. The same variables were monitored during a 40 minute period at 1.0 MAC SEVO for each bird. Mean MAC was 3.0±0.6 per cent for SEVO. During maintenance of anaesthesia at 1.0 MAC, SAP decreased significantly (P<0.001) without any significant change in HR. Although PE′CO2 increased significantly (P=0.001) despite an increase in f R, awake PE′CO2 values were unexpectedly low. Sinus arrhythmias were detected in two birds under SEVO anaesthesia. The times to tracheal intubation and to recovery were 2.5±0.7 and 6.4±1.7 minutes, respectively. Recovery was rapid and uneventful in all birds. In conclusion, SEVO is suitable for anaesthesia in pigeons.